The Status of Soft Law in Interpreting the Lithuanian Constitution - Murauskas, Donatas (Teisė, 2021)
In this paper, I examine the status of soft law in the official interpretation of the Lithuanian Constitution. The “living constitution” doctrine dominates the Lithuanian constitutional scholarship. I question this dominance by providing insights on the essence and application potential of the alternative methodology – the doctrine of originalism. Based on originalistic approach, I doubt the normative claim made in Lithuanian constitutional scholarship that soft law could be considered as a mandatory source of interpretation of the Lithuanian Constitution.